PERSEPSI SISWA KELAS VI SEKOLAH DASAR TENTANG PERUBAHAN YANG TERJADI SELAMA MASA PUBERTAS - Rohmayanti, Rohmayanti; Hermayanti, Yanti; Mardiah, Wiwi (Journal of Holistic Nursing Science, 2016)
Puberty is a time of transition from childhood to the teenage years. In the face of puberty, teenager will perceive these changes with different points of view in accordance with the experience, knowledge and motivation they have. Adolescent perception of this change will form a pattern of attitudes and behavior of adolescents especially related to adolescent reproductive health. This study aims to understand adolescent health issues from the perspective of adolescent perception itself. This type of research is descriptive qualitative approach. Informants in this study involved six students were taken by purposive sampling. The process of collecting data using interviews, all data contained in matrix form and explained in the narrative. The process of data analysis was done by reviewing all data, reduce the data, find a theme and make interpretation of research results. The results showed that most informants perceive changes in puberty as a scary thing and build an embarrassment to the physical changes such as menstrual events, voice changes, and changes in body weight, which is expressed by four informants. This condition causes the student is impaired in social relations (psychosocial) in the area of ​​family, peers and school. Those that perceive that change as a normal thing that is not to be feared. This causes the tendency of informants develop a negative perception of the changes in puberty. Perception of these students in the wake of many things, including knowledge inadequate, therefore the necessary co-operation between parents, teachers and health workers to take an active role in efforts to provide guidance to adolescent health issues, where nurses can play a role as an educator, counselor and motivator.